Work Ethics, Progressive Discipline, and Work Engagement on Job Satisfaction of Labuhanbatu District Education Service Employees - Zulkarnain Zulkarnain; Pitriyani Pitriyani; Abd. Halim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research was conducted at the Labuhanbatu Regency Education Office, with the aim of analyzing the influence of work ethics, progressive discipline, and work involvement on employee job satisfaction. This research uses quantitative methods with several analytical techniques such as classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination testing. The results of this research state that all independent variables have a positive and significant influence on the dependent variable. This can be proven by the work ethics variable (X1) which has a value of t count (7.26) > t table (1.66), which means that Ha is accepted and Ho is rejected. Meanwhile, the significant value is smaller than the probability value of 0.05 or the significant value of 0.000 < 0.05. Thus, the work ethics variable (X1) has a positive and significant effect on employee job satisfaction (Y). Progressive discipline (X2) has a value of t count (6.65) > t table (1.66) which means Ha is accepted and Ho is rejected. Meanwhile, the significant value is smaller than the probability of 0.05 or 0.000 < 0.05. Therefore, progressive discipline (X2) has a positive and significant effect on employee job satisfaction. Work involvement (X3) has a value of t count (11.26) > t table (1.66) which means Ha is accepted and Ho is rejected, while the significant value is smaller than the probability of 0.05 or 0.000 < 0.05. Thus, work involvement (X3) has a positive and significant effect on employee job satisfaction. Meanwhile, the F test has an F count value of 87.27 > F table 2.70 with a significance value of 0.000 < 0.05. From these results, it can be concluded that work ethics (X1), progressive discipline (X2), and work involvement (X3) simultaneously have a positive and significant effect on employee job satisfaction (Y).